Impact of clinical factors and surgical outcome on long‐term survival in high‐grade serous ovarian cancer: a multicenter analysis. Issue 5 (May 2021) - Baum, Joanna; Braicu, Elena Ioana; Hunsicker, Oliver; Vergote, Ignace; Concin, Nicole; Van Nieuwenhuysen, Els; Feldheiser, Aarne; Achimas‐Cadariu, Patriciu; Darb‐Esfahani, Silvia; Berger, Astrid; Fetica, Bogdan; Mahner, Sven; et al.
Abstract : Introduction : Long‐term survivors of ovarian cancer are a unique group of patients in whom prognostic factors for long‐term survival have been poorly described. Such factors may provide information for a more personalized therapeutic approach. The objective of this study is to determine further characteristics of long‐term survivors with high‐grade serous ovarian cancer. Methods : Long‐term survivors were defined as patients living longer than 8 years after first diagnosis and were recruited within seven high volume centers across Europe from November 1988 to November 2008. The control group included patients with high‐grade serous ovarian cancer with less than 5 years' survival identified from the systematic 'Tumorbank ovarian cancer' database. A subanalysis of Charité patients only was performed separately for in‐depth analysis of tumor dissemination. Propensity score matching with nearest‐neighbor caliper width was used to match long‐term survivors and the control group regarding age, FIGO stage, and residual tumor. Results : A total of 276 patients with high‐grade serous ovarian cancer were included, divided into 131 long‐term survivors and 145 control group patients. After propensity score matching and multivariable adjustment, platinum sensitivity (p=0.002) was an independent favorable prognostic factor whereas recurrence (p<0.001) and ascites (p=0.021) were independent detrimental predictors for long‐term survival. Significantly more long‐term survivors tested positive for mutation in the BRCA1 gene than the BRCA2 gene (p=0.016). Intraoperatively, these patients had less tumor involvement of the upper abdomen at initial surgery (p=0.024). Complexity of surgery and surgical techniques were similar in both cohorts. Conclusion : Platinum sensitivity constitutes a favorable factor for long‐term survival whereas tumor involvement of the upper abdomen, ascites, and recurrence have a negative impact. Based on clinical estimation, long‐term survival is associated with combinations of clinical, surgical, and molecular factors.